Práticas de gestão do conhecimento pessoal para desenvolvimento individual, coletivo e organizacional em prol da inovação em organizações intensivas em conhecimento - Lima, Mariana Rodrigues de (2025)
In the current context, marked by technological acceleration and constant changes, Knowledge-Intensive Organizations KIOs face significant challenges in maintaining their competitiveness and innovation capacity. In this context, Personal Knowledge Management (PKM) emerges as a set of practices that enables knowledge workers to manage learning, sharing, and applying knowledge in a strategic way, practices that contribute to professional excellence and foster organizational innovation. This research aimed to identify how the PKM practices adopted by knowledge workers in knowledge-intensive companies influence individual development, knowledge management and innovation in these organizations. The methodology used descriptive and qualitative research, based on semi-structured interviews conducted with professionals from nine Brazilian KIOs. The interviews were analyzed through the content analysis technique, allowing the identification of PKM practices, their impacts on the organizational environment and the challenges faced by the participants. The study covered various sectors, prioritizing organizations that work intensively in the use of knowledge as a strategic resource. The main results indicate that PKM works as a catalyst for continuous learning, promoting alignment between individual and organizational objectives and contributing to incremental improvements in processes and products. It was also identified that PKM practices positively influence the sharing of tacit and explicit knowledge, in addition to fostering collaboration through communities of practice and internal networks. However, institutional gaps, such as the lack of alignment between individual practices and Knowledge Management policies and challenges such as time management and prioritization of objectives, end up limiting the effectiveness of PKM in some organizational contexts. It is concluded that PKM is essential for individual, collective and organizational development in KIC, strengthening adaptability and innovation. As a contribution to the Academy, the research expands the understanding of the relationship between PKM, Knowledge Management, and innovation, in addition to offering subsidies for professionals and managers interested in promoting more effective strategies to manage the knowledge of individuals and teams in KIOs.